Characterisation of Lacto-Fermented Cricket (Acheta domesticus) Flour and Its Influence on the Quality Parameters and Acrylamide Formation in Wheat Biscuits - Bartkiene, Elena (2023)
The aim of this study was to evaluate the influence of different amounts (40, 80 and 100 g) of non-fermented and fermented (with Lactiplantibacillus plantarum No. 122 and Lacticaseibacillus casei No. 210) cricket flour (Cr) on the quality characteristics and acrylamide formation in wheat biscuits (WB). The main formula for WB preparation consisted of 280 g of wheat flour, 100 g of margarine, 50 g of saccharose, 3 g of vanilla sugar, 50 g of eggs, 1.5 g of salt and 2.0 g of baking powder. It was established that the highest lactic acid bacteria (LAB) number was achieved in 48 h with No. 122 fermented Cr (11.8 log10 CFU/g) and the lowest pH (4.34) was obtained after 48 h of Cr fermentation with both the tested LAB strains. The total colour differences were in the range of 17.54 to 22.08 and, in every case, fermented samples were clearly distinguished from untreated ones. Fermentation increased tyramine content in Cr (from 13.0 to 29.2 times). The main FAs in Cr were palmitic acid, stearic acid, octadec-9-enoic acid and linoleic acid. The lowest acrylamide content (84.1 µg/kg) was found in WB with 40 g of Cr fermented with No. 210. Significant differences in WB overall acceptability were not found. However, the highest intensity of emotion “happy” was elicited by WB with 80 g of Cr fermented with No. 122. Due to the demonstrated decrease of acrylamide content, fermented Cr can be considered a beneficial ingredient for the manufacture of WB.